Comparison of Patients’ Outcome Having Anterior Wall Myocardial Infarction with & without Right Bundle Branch Block Undergoing Primary Percutaneous Coronary Intervention in Terms of Major Adverse Cardiovascular Events at 30-Days Follow-up - Muhammad Ayaz Arshad, Muhammad Ahsan Fareed, Maham Riaz, Tariq Saleem, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Acute anterior wall myocardial infarction (AWMI) is frequently complicated by a number of complications, and right bundle branch block (RBBB) is an uncommon association leading to higher morbidity and mortality rates. Objectives: To compare the 30-day outcomes of MACE in participants presenting with anterior wall MI having RBBB pattern versus patients presenting with non-RBBB pattern on ECG undergoing primary PCI. Study Design: In-hospital, prospective, comparative, and observational study. Duration and Setting: Faisalabad Institute of Cardiology (FIC) between January and December 2022. Methodology: A total of 204 patients with AWMI undergoing pPCI were recruited. Post-PCI follow-ups of the patients were carried out as by direct observation and telemonitoring of the patients and one-to-one interviews if required, during the hospital stay and after discharge patients were requested for a follow-up visit in the OPD, and in case the patient was unable to come, a telephone call was made for follow-up. SPSS v26 was utilized for data analysis. Among 204 patients, 68 (33.3%) had RBBB and were relatively younger. AWMI was more common in males (86.3%). RBBB was more frequent in males (88.2%), while females more often had AWMI without RBBB (14.7%). Smoking was the leading risk factor with RBBB (47.1%, p=0.045), hypertension without (47.1%, p=0.094). In-hospital (5.9%) and 30-day (10.29%) mortality, Re-MI (17.6%), and heart failure (35.3%) were higher in RBBB. CVA was higher without RBBB (2.9%). Conclusion: We inferred that in the patients with AWMI undergoing pPCI, there is an increased risk of 30-day mortality if the RBBB complicates the AWMI. Keywords: Anterior Wall Myocardial Infarction, Right Bundle Branch Block, Primary Percutaneous Coronary Intervention, Major Adverse Cardiovascular Events, 30-day Follow-up